Monetary policy and the distribution of income: Evidence from U.S. metropolitan areas - Giovanni Favara; Francesca Loria; Egon Zakrajšek (Federal Reserve Bank of Boston, 2025)
We use Zip code-level Statistics of Income data from the Internal Revenue Service to measure the distribution of income within U.S. metropolitan areas from 1998 through 2019. Exploiting geographic variation in income distribution over time, we study how unanticipated changes in the monetary policy stance shape the subsequent dynamics of income inequality. The results show that monetary policy persistently affects labor income inequality and that these distributional effects are amplified significantly in weak local labor markets.
Keywords: E21; E52; E58; 330; Income inequality; distributional impact of monetary policy; high-frequency monetary policy surprises; local labor markets